Research with International Students Critical Conceptual and Methodological Considerations - Mittelmeier, Jenna; Lomer, Sylvie; Unkule, Kalyani (Internationalization in Higher Education Series, 2024)
This must-read book combines carefully selected contributions to form a collective scholarly critique of existing research with international students, focusing on key critical and conceptual considerations for research where international students are participants or co-researchers. It pushes forward new agendas for the future of research with international students in global contexts, posing new sets of problems, provocations, and possibilities. Bringing together a range of interdisciplinary scholars, this book explores the many facets of research, which centres international students and their experiences. Each chapter concludes with practical reflection questions, suggestions for researchers, and examples in existing research to support research designs and aid in developing high-quality, critical research on this topic. Bringing fresh perspectives to the topic of research with international students, the book focuses on: Outlining current problems with existing research, including the ways that international students may be stereotyped, homogenised, Othered, or framed through deficit and colonial narratives (Re)-conceptualising key ideas that underpin research which are currently taken for granted Developing reflection points and practical guidance for new research designs which centre criticality and ethics Outlining ways that discourses and narratives about international students can be made more complex, particularly in reflection of their intersectional identities This key text is essential reading for researchers at all career stages to reflect on issues of power, inequality, and ethics, whilst developing understandings about critical choices in research design, analysis, and the presentation of findings.